Analisis Faktor Cuaca dengan Kejadian Demam Berdarah Dengue (DBD) di Kabupaten Wonogiri Tahun 2014-2018 - Endah Nur Latifah; Yusniar Hanani Darundiati; Nur Endah Wahyuningsih (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Wonogiri Regency is one of the dengue endemic areas in Central Java with a fluctuating number of cases during 2014-2018. The number of dengue cases drastically increased nearly 4 times amounting 52 cases in 2016 to 207 cases in 2017. Weather factors such as rainfall, humidity, temperature, and wind velocity can affect the reproduction and spread of DHF vectors. Objectives: This study was aimed to analyze the association between weather factors (rainfall, humidity, temperature and wind velocity) with the incidence of dengue fever in Wonogiri Regency in 2014-2018. Research Metodes: This research was an analytic observational study using cross sectional approach. The type of data used was secondary data about the weather (rainfall, humidity, temperature and wind velocity) in Wonogiri Regency which was obtained from the Wonogiri Meteorological Station and data on the number of dengue incidents in Wonogiri Regency which were obtained from the Health Office of Central Java Province. The data were used each month for 5 years, from January 2014 to December 2018. Data were analyzed by using univariate and bivariate analysis (Rank Spearman correlation test), because only the humidity variable is normally distributed. Results: The highest number of dengue cases during 2014-2018 as many as 30 cases in November 2018 with an average of 6 cases, the highest rainfall was 887 mm with an average 191.05 mm, the highest humidity was 91.55% with an average of 86.77%, the highest temperature was 28.75oC with an average of 27.50oC and the highest wind velocity was 7.86 knots with an average of 0.89 knots. The results of the Spearman Rank correlation statistical test showed that there was a significant association with moderate strength and a positive direction between rainfall and the incidence of DHF (p = 0.001 and r = 0.420), which means that the increasing of rainfall, the more the number of DHF incidents. There was no significant association between humidity and the incidence of dengue fever (p = 0.925 and r = 0.012). There is a significant association with moderate strength and a negative direction between temperature and the incident of DHF (p = 0.001 and r = -0.415), which means that the increasing the temperature, the number of dengue cases decreases. There is no significant association between wind velocity and the incident of dengue (p = 0.577 and r = -0.073). Conclusion: Rainfall causes the breeding place of Aedes mosquitoes to increase, as a result it has an effect on the increase of the mosquito population. Temperature affects the number of eggs produced by Aedes mosquitoes, so that the density of adult mosquitoes increases.